Kepastian Hukum dalam Penanaman Modal Investasi di Kawasan Ekonomi Khusus dari Perspektif Investor - Anis Retno Triana; Annisa Amelia Putri; Kamala Mar’atussholikhah; Verga Syaharani Sukma; Firdaus Firdaus; Muhammad Fajar Hidayat (Lembaga Pengembangan Kinerja Dosen, 2024)
Special Economic Zones (SEZs) in Indonesia serve as strategic instruments to attract domestic and foreign investments and accelerate economic growth in specific regions. Legal certainty within SEZs, encompassing regulatory stability, transparent licensing procedures, and effective legal protection, plays a crucial role in shaping investor perceptions and decisions. This research employs a normative juridical research method, focusing on the study of applicable legal norms or rules to analyze, interpret, and examine relevant legal principles. The findings indicate that investor perceptions of legal certainty are significantly influenced by regulatory complexity and consistency, transparent licensing procedures, and adequate legal protections. Investors tend to favor investment environments offering clear regulations, efficient licensing processes, and robust legal protections to mitigate investment risks. Based on these findings, it is recommended to enhance regulatory transparency and consistency, streamline licensing processes, strengthen legal protections, and improve investor education on SEZ regulations and legal protections. These steps are expected to enhance the attractiveness of SEZs as competitive and sustainable investment destinations, contributing significantly to regional economic growth.